Perancangan Sistem Antrian dan Penentuan Jumlah Operator SPBU untuk Mengurangi Panjang Antrian dan Total Biaya Operasional dengan Metode Simulasi - Liputra, David Try; Suhada, Kartika; Arisandhy, Vivi; Bakti, Nelson Karunia (Universitas Teuku Umar, 2024)
Improving and enhancing the performance of both service and manufacturing systems is essential for achieving customer satisfaction with the service. Research on improving and enhancing the performance of gas stations, whether using simulation methods or combinations with other methods, has been extensively conducted. However, studies that focus on improving the queue system at gas stations using simulation methods to reduce queue length and total operational costs are still limited. Previous research has proposed changes in the combination of fuel types at nozzles and the number of operators working per shift to reduce operational costs. However, these studies did not consider the resulting queue lengths. Therefore, this study will propose a design for the queue system and determine the number of operators to reduce queue length and total operational costs. First step, a simulation model of the actual queue system is created. Next step, alternative scenarios are developed for fuel type allocation at each nozzle and for determining the number of operators. Then, a simulation model of the queue system for each scenario is created. The final step is to calculate the queue length and total operational costs for the actual and proposed queue systems. There are 5 alternative scenarios to reduce the number of operators, with the best alternative being scenario 5. Scenario 5 also results in a shorter average vehicle queue length and lower total operational costs compared to the actual queue system. The average vehicle queue length decreased by 0.52 units or 31.71%. Additionally, the total operational cost decreased by Rp 714,717.74, or 23.24%.